HAKIKAT HAK MASYARAKAT HUKUM ADAT DALAM OMNIBUS LAW DI INDONESIA - Sumadi Sumadi; Ahmad Rifai Rahawarin Rifai Rahawarin; Muh. Amin Hamid; Desy Maryani (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2022)
Abstract: The purpose of this article is to understand and analyze the essence of the rights of indigenous and tribal peoples in omnibus law through a juridical study with a philosophical approach, a conceptual approach, and a statutory approach. Whereas the essential rights of indigenous peoples are the rights to justice and the value of welfare for the utilization of natural resources of indigenous peoples who are not yet maximized which is expected in the work copyright law to provide justice and welfare for indigenous peoples over exploited customary areas. Keywords: Rights; Indigenous Peoples; Omnibus Law.